Menelusuri Pemetaan Komunikasi Pemasaran Kontekstual - Purtiwi, Narita Putri (Jurnal Studi Komunikasi, 2018)
Marketing, a context which is the core of what was conveyed in the Contextual Marketing Communication book. In industry and business in this era, it had faced the colors of culture and environment and even face a revolution like a massive change from digital. Various marketing strategies are initiated to understand the flow of people's desires. But there are still contradictions that do not reflect contextual itself.